PENGGUNAAN KATA SAPAAN DALAM RANAH KESANTUNAN BERBAHASA PADA MASYARAKAT JAWA DESA LANGKANG LAMA KECAMATANPULAU LAUT TIMUR KABUPATEN KOTABARU (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
ABSTRACTThe purpose of this study is (1) to know the types of greetings in the field oflanguage politeness in the community of Java Village Langkang Lama KecamatanPulau Laut TimurKabupaten Kotabaru, (2) to know the use of the word greeting inthe field of language politeness in the community of Java Langkang Lama VillageKecamatan Pulau Laut Timur of Kabupaten Kotabaru, (3) to know the PublicCommunication by using the word greeting in the sphere of politeness language inthe community of Java Langkang Lama Village, Kecamatan Pulau Laut Timur,KabupatenKotabaru .The method used in this research is descriptive qualitative research methodsthat describe the objective and actual stages of the at the time of communication.While this type of research is a case study in which the study is about an activity ofa society that aims to understand the object being studied.The result of the research shows that (1) The use of the word greeting in theSpeech Language Speech in Java Community Langkang Lama Subdistrict of PulauLaut TimurKabupaten Kotabaru there are 3 types of greeting that is greeting thename of self, greeting kinship and greeting non-kinship, (2) Use of Greeting insphere Speech Language used by the Community of Java Langkang Lama VillageDistrict of Pulau Laut Timur Kabupaten Kotabaru is the use by self-name, the useof kinship greeting consists of mbah lanang, mbah wedok, pak'e, mak'e, kakang,iyu, adek, call the name, adek, name, thole, ndok, pak'de, bu'de, pak'lek and bu'lek.The use of non-friendship greeting consists of mbah, mbah, pak'lek, bu'lek, kakang,iyu, name, mention name, adek, adek, pak lurah and pak RT. And (3) CommunityCommunication by Using Greeting Speech in Speech Language Speech in JavaCommunity Langkang Lama Kecamatan Pulau Laut Timur Kabupaten Kotabaruusing two types of Java language, the Ngoko Java language and Javanese Krama.Keywords: Greetings, Speech Language and Java Society.